The Precious Door of the Pamplona Cathedral: An Iconographic Interpretation Based on Apocryphal Sources - Salvador González, José María (Eikón / Imago, 2012)
This article seeks to highlight if and to what extent the mastermind of the Precious Door in the cloister of the Pamplona Cathedral is directly inspired by the apocryphal literature. The in-depth study of a dozen apocryphal texts leads us to conclude that almost all the episodes, characters, situations and objects represented in this portal somehow illustrate the essence of one or other of the main passages of these ten legendary writings. Through comparative analysis of texts and images, we can conclude that the author of this portal frequently mixes the contributions of the various apocryphal, no matter the consistency between them. Furthermore, a thorough reading of these apocryphal legends does not allow to decipher the precise meaning of certain characters and episodes of this portal, ultimately remaining ambiguous or enigmatic.